Indigenous Microbiota to Leverage Traditional Dry Sausage Production - Noelia Zulema Palavecino Prpich; Germán Edgardo Camprubí; María Elisa Cayré; Marcela Paola Castro (International Journal of Food Science)
The main issue addressed in this review is the need for innovation in the artisanal production of dry fermented sausages—leveraging rather than discarding tradition, together with some practical strategies available to achieve it. Throughout the text, emphasis is placed on the autochthonous microbiota responsible for the identity and unique sensory characteristics of these products. The available strategies to introduce innovation in this manufacturing process rely on metabolic flexibility of microbial strains. In this sense, this review evaluates the application of several tools aimed at improving the quality and safety of artisanal dry fermented sausages focusing on the microbial community role. The most studied alternatives to enhance dry sausage production comprise the use of autochthonous starter cultures—including functional and/or probiotic strains, the production of bacteriocins, and the generation of bioactive peptides, which have been thoroughly covered herein. The purpose of this work is to review recent research about novel different strategies available for food technologists to improve safety and quality in the manufacture of dry fermented sausages. Additional support strategies—quality product registers and innovation through tradition—have been suggested as complementary actions towards a successful introduction of indigenous microbial communities into traditional dry sausage production.